ENSURING THE SUSTAINABILITY OF PUBLIC FINANCES IN THE CONDITIONS OF SOCIAL AND ECONOMIC INSTABILITY - KHRUSHCH, Nila; NIANKO, Lyudmila (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the article is research and assessment of the stability of public finances as a component of the financial system of the state in conditions of instability. Early detection of threats to the stability of economic development and timely prevention of crisis situations is one of the most important long-term goals of the economic policy of the government of any country. The theoretical aspects of the public finance system are considered, namely: their essence, functions and structure, as well as the modern public finance system of Ukraine, its structure and component links. Public finance is a key component of the financial system of Ukraine, which owns more than half of all financial resources and includes various financial institutions that implement the functions of the state. Ensuring public finances is an institutional process, which consists in the implementation of structural transformations of their components to ensure the effective accumulation and distribution of public financial resources in accordance with the priorities of the country’s socio-economic development. The practical aspects of the application of modern tools for assessing the sustainability of public finances in the conditions of Ukraine are revealed. The evolution of approaches to defining the concept of "sustainability" is presented. The multi-functionality of public finances determines their extensive structure, the main component of which is the State budget. The article analyzes the implementation of the State Budget of Ukraine for nine years (2013-2021), as a key component of public finances and one of the criteria for their sustainability, and determines the level of the budget deficit and its share in GDP. It is shown that the budget indicators almost correspond to the European criteria for the sustainability of the public finance system. A manifestation of the instability of the state’s financial position is, as a rule, an unlimited increase in the relative value of the state debt (no more than 60% of GDP). An inevitable consequence of the instability of public finances is hyperinflation and/or the state’s refusal to service its obligations (default). Based on calculations, it was found that the level of the state debt met these requirements only in 2019 and 2021. The need to maintain the ratio of public debt to GDP at a constant level to ensure financial stability is argued by the fact that the amount of public debt, which is constantly growing, may soon reach a certain limit, which will be perceived as the solvency threshold.